Couvrez cette communauté que je ne saurais voir: Equity and Fault in the Division of Quebec’s Family Patrimony - Kasirer, Nicholas (Revue générale de droit, 1994)
An inquiry into the role of fault in divorce may be taken as an invitation, for the Quebec jurist, to evaluate the place of misconduct in petitions for unequal “partition'' of the family patrimony. The author proposes an analysis of article 422 of the Civil Code of Québec based on a comparison with the law of family property in common law Canada. He observes a disinclination, felt in Quebec legal circles, to explore the connections between recourses under Quebec law for unjust enrichment in marriage and parallel remedies in common law. Basing himself principally on a review of rules similar to article 422 in Ontario law, he contends that a court should not allow ordinary measures of spousal misconduct to influence petitions for the unequal division of the family patrimony. Connecting the family patrimony to the statutory remedies for unjust enrichment in Ontario matrimonial law reveals a narrow idea of economic fault that underlies the judicial discretion at article 422 C.C.Q.